Monitoring of Ambient Air Quality of Patiala City With Special Reference to Crop Residue Burning - Singh, Nirankar (My University, 2011)
Development of an effective agricultural crop residue management plan in the Northwest region of India has been hindered by the lack of awareness and information about the adverse impact of agricultural residue burning practices on regional ambient air quality. These practices emit SPM and gaseous species into the atmosphere influencing health and materials in the area. Open wheat (Triticum aestivum) and rice (Oriza sativa) crop stubble burning events are observed in and around Patiala city during April-May and October-November every year. A study involving ground level measurements was conducted to analyze the contribution of wheat and rice crop stubble burning practices on concentration levels of suspended particulate matter (SPM), Oxides of sulphur and nitrogen (SO2 and NO2) were monitored in the ambient air at five different sites in and around Patiala city covering agricultural, commercial and residential areas. Aerosol samples were collected on GMF/A and QMF/A (Whatman) sheets using High Volume Sampling (HVS) units for a 24 h period throughout the study period covering four rice and three wheat crop harvesting seasons from 2006-2010. Simultaneously, sampling of SO2 and NO2 was conducted and results obtained during stubble burning periods were compared with the non-stubble burning periods. Interesting results were obtained during this course of study. Results pointed out a distinct increase in aerosol, SO2 and NO2 levels during the crop stubble burning periods. Further, SPM samples were analyzed for the determination of organic tarry matter (OTM), loss on ignition (LOI), heavy metals and poly aromatic hydrocarbons (PAHs). Results indicated a clear impact of crop residue burning practices in Northern India. Average levels of LOI pointed to the presence of a high content of combustible matter in the ambient air of Patiala. It has been observed that levels of combustible matter content were associated with the levels of SPM integrated with the effect of crop residue burning (CRB) practices in the region. SPM samples were analyzed for Dichloromethane (DCM) soluble fraction and concentration levels of OTM were observed. Levels of LOI and OTM were also associated with the CRB episodes. SPM samples were further analyzed for the concentration levels of potassium (K) and some heavy metals like copper (Cu), nickel (Ni) and zinc (Zn) and the results are compared with the crop residue burning (CRB) and non-crop residue burning (NCRB) months. Significant association was obtained in the ambient air levels of SPM and K. High concentration levels of K was obtained during agricultural burning seasons of wheat and rice crops. Heavy metals like Cu, Ni and Zn were associated with the similar range of concentration but no relationship was obtained with CRB episodes. Although, increase in K levels was observed at all the sites, but a strong association in K levels and CRB was obtained at an agricultural area site only. Higher concentration levels of polycyclic aromatic hydrocarbons like benzo (k) fluoranthene (45.33 ppm in April 2007) and pyrene (0.58 ppm in November 2007) were also observed during episodic crop residue burning events for the duration of April-May and October- November. Significant increase in the concentration levels of PAHs was obtained at commercial and agricultural area sites. However, the existence of variations could be attributed from factors such as site characteristics, topography of surrounding area, types and frequency of vehicles plying on the roads, types of biomass burned, etc. The meteorological factors such as wind speed and direction, relative humidity, atmospheric pressure and temperature have also influenced the levels and flow of air pollutants in the study area.
Ph.D. (SCBC)
Keywords: Ambient Air Quality; Crop Residue Burning